Impacts of Long-Term Flood-Induced Sedimentation on Agricultural Land: Case Study of the 2008 Koshi Flood in Eastern Nepal - Kafle, Kumud Raj; Khanal, Sanjay Nath; Dahal, Ranjan Kumar (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Flood of August 2008 in eastern lowlands of Nepal affected around 2.64 million people in India and Nepal, including 65,000 people and 700 ha fertile land in Nepal. It was estimated that 20% of land was still barren even in 2016 (eight years after the flood). The long-term effect of flood-fed sedimentation in context of agriculture practices is the focus of this research. Information from questionnaire survey, field measurement and lab analysis are the adapted methods for the assessment. The affected area is divided into four zones with respect to the depths from 0.10 m to 5.0 m. The area where sedimentation thickness is less than 0.5m is in manageable condition within a year and in between 0.5m to 1.5m thickness could not be suitable for traditional crop even after 8 years. The thickness existed more than 2m is not suitable for any crop even after the 8 years because of its long-term impact on cultivation in context of flood-fed sedimentation and recovery. From Normalized Difference Vegetation Index (NDVI) analysis also indicated that the recovery with vegetation trend is about 10% per year in less than 2m of thick sedimentation zones. Size of sediments and sedimentation thickness are the significant parameters to recover flood-fed sedimentation zone.